Ready to fly? Comparing acceptance and behavioral usage intentions of CO2-based aviation fuels in four European countries - Arning, Katrin; Engelmann, Linda; Ziefle, Martina (Frontiers in Energy Research, 2023)
Significantly increased global greenhouse gas emissions from aviation make the decarbonization of the aviation sector an urgent demand to combat climate change. One technical approach is the usage of Carbon Capture and Utilization technologies (CCU) to re-use CO2 as raw material and to produce CO2-based aviation fuels. As the social readiness is an essential component for a successful roll-out, this study investigates acceptance and behavioral usage intentions regarding CO2-based aviation fuels. We applied an empirical quantitative online questionnaire in four European countries (Spain, Norway, Netherlands, and Germany, N = 2187). To get a comprehensive overview of the factors that predict social readiness, data on relevant impact factors were collected, including sociodemographic factors, awareness, attitudinal factors (innovation cautiousness, environmental awareness, flight shame), flight behavior as well as evaluations in terms of benefit and risk perceptions of CO2-based fuels. Employing hierarchical regression analyses we identified the impact of individual factors and fuel-related perceptions on the acceptance of and the willingness to use CO2-based aviation fuels. For the prediction of CO2-based fuel acceptance, benefit perceptions were the strongest predictor, followed by environmental awareness, risk perceptions, interest, and flight shame. For the behavioral intention to fly with CO2-based fuels, benefit perceptions showed the strongest impact, followed by environmental awareness, interest, and risk perceptions about technical quality and -maturity as well as health- and environmental risks. This was valid for all four European countries under study, even though there were also national differences: Norwegian respondents showed the lowest interest in and knowledge of CO2-based aviation fuels and the lowest acceptance. Spanish respondents reported the highest acceptance, while acceptance scores of German and Dutch residents ranged in between. Overall, the findings provide a pan-European insight into the social readiness for CO2-based aviation fuels and its determinants, providing targeted information on public adoption conditions and requirements for CCU technology developers and the aviation industry.